Photoelectrochemical activities and low content Nb-doping effects on one-dimensional self-ordered Nb2O5–TiO2 nanotubes. Issue 12 (11th February 2015) - Pei, Linjuan; Yang, Min; Zhang, Dan; Zhang, Lei; Chen, Peng; Song, Yanyan; Gan, Yang
<x xml:space="preserve">Abstract</x> Nb2O5-doped TiO2 nanotube arrays were fabricated by anodization. Nb's beneficial effects exhibit an improved charge separation efficiency, resulting in higher photocatalytic/photoelectrocatalytic activities.